2017
DOI: 10.1186/s12888-016-1178-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 10-item Centre for Epidemiological Studies Depression Scale (CES-D-10) in Zulu, Xhosa and Afrikaans populations in South Africa

Abstract: BackgroundThe 10-item Centre for Epidemiological Studies Depression Scale (CES-D-10) is a depression screening tool that has been used in the South African National Income Dynamics Study (NIDS), a national household panel study. This screening tool has not yet been validated in South Africa. This study aimed to establish the reliability and validity of the CES-D-10 in Zulu, Xhosa and Afrikaans. The CES-D-10’s psychometric properties were also compared to the Patient Health Questionnaire (PHQ-9), a depression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 31 publications
6
181
0
1
Order By: Relevance
“…While the WHO estimates that 42% of the South African population is hypertensive, 32% have elevated levels of LDL and 11% with elevated blood glucose levels 27, these data found the prevalence of HTN to be 33.3%, LDL 19.8% and elevated blood glucose 3.9%. While study limitations restrict direct comparison to national datasets, obesity, HTN and elevated LDL levels appear to present a significant disease burden in this community.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While the WHO estimates that 42% of the South African population is hypertensive, 32% have elevated levels of LDL and 11% with elevated blood glucose levels 27, these data found the prevalence of HTN to be 33.3%, LDL 19.8% and elevated blood glucose 3.9%. While study limitations restrict direct comparison to national datasets, obesity, HTN and elevated LDL levels appear to present a significant disease burden in this community.…”
Section: Discussionmentioning
confidence: 90%
“…A short form Patient Health Questionnaire (PHQ‐9) score of ten or more was used as the standard cut‐off indicating major depressive symptoms 25. The PHQ‐9 has been previously validated for use among all ages of the South African population 26, 27, 28.…”
Section: Methodsmentioning
confidence: 99%
“…For example, minimum sample size requirements at least doubled when moving from one to two factors CFA [34]. A review of the literature of published CES-D-10 validation studies revealed that except for one study with over 16,000 participants [20], sample sizes for one factor solution varied from as low as 47 to 755 [11,18,19,21,3539]. Also, two studies with sample sizes of 1013 and 742 reported a two factor solution [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…While the published validity studies of the CES-D-10 illustrated acceptable factorial validity there were indications that the factorial structure has not been consistently determined. For example while studies among adults in Zulu, Xhosa and Afrikaans in South Africa [19] and the USA Hispanics population [20] concluded a one factor solution had the best model fit, studies in Canadian adolescents [21] and Singaporian elderly [16] resulted in a two-factor model and validation studies in older Chinese populations [17,18] reported two-factor and three-factor models of the CES-D-10 respectively. These contradictory findings may be due in part to the use of: i) individuals with different cultural background; ii) differences in study sample age ranges; iii) participant characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on measures self-reported by the participants and collected in every wave of the NIDS. The CES-D scale has been used in a wide set of longitudinal studies and is a validated measure for the poorer populations living in South Africa [6].…”
Section: Mental Health Measurementioning
confidence: 99%